2021
DOI: 10.3389/fonc.2021.562315
|View full text |Cite
|
Sign up to set email alerts
|

Response Efficacy of PD-1 and PD-L1 Inhibitors in Clinical Trials: A Systematic Review and Meta-Analysis

Abstract: BackgroundImmune checkpoint inhibitors targeting the PD-1/PD-L1 pathway have demonstrated promise in treating a variety of advanced cancers; however, little is known regarding their efficacy under various clinical situations, including different cancer types, treatment lines, drug combinations, and therapeutic regimens.MethodsPublished articles and conference abstracts (in English) in PubMed, Embase, the Cochrane Central Register, and Web of Science were searched up to February 10, 2020. The data were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 109 publications
(29 reference statements)
0
46
0
Order By: Relevance
“…In our study, seven patients developed PD after only two cycles of immunotherapy-based therapy, which may be due to the early resistance to the combined agents rather than ICI. Previous studies showed a delayed onset of action of ICIs with a median time to response of 2.05–3.3 months (Chen et al 2021 ; Hida et al 2017 ; Rizvi et al 2015 ). After re-administration of ICI and change of the combined regimens, these patients responded well.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, seven patients developed PD after only two cycles of immunotherapy-based therapy, which may be due to the early resistance to the combined agents rather than ICI. Previous studies showed a delayed onset of action of ICIs with a median time to response of 2.05–3.3 months (Chen et al 2021 ; Hida et al 2017 ; Rizvi et al 2015 ). After re-administration of ICI and change of the combined regimens, these patients responded well.…”
Section: Discussionmentioning
confidence: 96%
“…Compared to PD-1 inhibitors, PD-L1 inhibitors are usually not associated with significant conformational changes in PD-L1 [13]. Moreover, such discrepancies might be related to the substantial variations in the mechanisms of action of a single PD-1/PD-L1 blockade agent [15,38]. Based on discrepancies in the mechanisms of action between PD-1/PD-L1 inhibitors, more attention is being paid to the differences between anti-PD-1 and anti-PD-L1 treatments in clinical practice, and evidence-based analysis to understand their comparable efficacies is urgently required [15].…”
Section: Discussionmentioning
confidence: 99%
“…So far, Food and Drug Administration (FDA) has approved six monoclonal antibodies targeting PD1 (nivolumab, pembrolizumab, and cemiplimab) or PDL1 (atezolizumab, Durvalumab and avelumab) for the treatment of hematological and solid malignancies. ( Tan et al, 2016 ; Chen et al, 2021 ). Monoclonal antibodies (mAb), known as checkpoint inhibitors, overcome the shortcomings of traditional anticancer therapies and inhibit the PD1/PDL1 mutual effect.…”
Section: Mechanism Of Action and Treatment Of Pd1/pdl1 Inhibitorsmentioning
confidence: 99%
“…The anti-CTLA-4 antibody ipilimumab has shown durable anti-tumor activity and prolonged survival in patients with advanced melanoma, but is prone to immune-related adverse events (IAEs) ( Buchbinder et al, 2016 ). PD1/PDL1 inhibitors are promising immunotherapeutic agents that can achieve satisfactory efficacy for different tumor types, different treatment routes, different drug combinations and different treatment regimens ( Chen et al, 2021 ). The incidence of PD1/PDL1 inhibitor-mediated IAEs was significantly lower compared to CTLA-4 blockade ( Ott et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%